2017
DOI: 10.1111/tan.13186
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of classical HLA class I mRNA by allele‐specific, real‐time polymerase chain reaction for most Han individuals

Abstract: Recent studies have shown that expression levels of different alleles at the same HLA class I locus can vary dramatically, which might have a broad influence on human disease. However, precise quantification of the relative expression level of each HLA allele is challenging, because distinguishing different alleles on the same locus is difficult. Here, we developed a series of allele-specific, real-time polymerase chain reaction assays for quantifying HLA class I allele mRNA in most Han individuals. The allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…The drawback with previous protein expression studies has been the lack of allele-specific monoclonal antibodies to recognize all HLA alleles with equal affinity. While qPCR has been adopted for determining the expression of HLA alleles, the focus has been mainly on HLA class I ( 3 , 4 , 6 , 8 ). Given the high number of known HLA alleles, qPCR requires a combination of allele-specific primers to amplify different alleles of the same gene.…”
Section: Discussionmentioning
confidence: 99%
“…The drawback with previous protein expression studies has been the lack of allele-specific monoclonal antibodies to recognize all HLA alleles with equal affinity. While qPCR has been adopted for determining the expression of HLA alleles, the focus has been mainly on HLA class I ( 3 , 4 , 6 , 8 ). Given the high number of known HLA alleles, qPCR requires a combination of allele-specific primers to amplify different alleles of the same gene.…”
Section: Discussionmentioning
confidence: 99%
“…Taqman PCR and allele-specific real-time PCR are commonly used for ADE detection 48,49 . However, these methods suffer a major problem, i.e., it is difficult to distinguish two alleles on the same locus 2224 . Besides, two pairs of primers are used for these methods, which cause bias due to different amplification efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many approaches have been applied to determine ADE, such as high-throughput DNA/RNA sequencing 1218 , DNA microarray 1921 , Taqman PCR 22,23 , allele specific real-time PCR 24 , and digital PCR 25 . These methods lead to the detection of major genes associated with human disease, causal mutations in cis-regulatory elements, loss of function alleles, and others 2629 .…”
Section: Introductionmentioning
confidence: 99%
“…Real-time PCR has been adopted in several studies for determining the expression of HLA alleles, however, the focus has mainly been on HLA class I. [35,10] Given the high number of known HLA alleles, real-time PCR approach requires a combination of allele-specific primers to amplify different alleles of the same locus. Using RNAseq data of 50 individuals, we performed a high-throughput screen for HLA expression profiles of class I and class II alleles in peripheral blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Recently a few studies reported varying expression levels of HLA alleles based on the real-time polymerase chain reaction (PCR) and the mean fluorescence intensity (MFI). [310] The differential expression of HLA alleles has been associated with immunologically mediated diseases, such as Crohn’s disease [11] and HIV [6,12], follicular lymphoma[7], and the outcome of HSCT through the risk of graft versus host disease (GvHD)[8,9]. In fact, incompatibilities between the donor and the recipient in HSCT have made the expression differences of HLA molecules an interesting target for finding permissive mismatches.…”
Section: Introductionmentioning
confidence: 99%